2017
DOI: 10.7205/milmed-d-17-00063
|View full text |Cite
|
Sign up to set email alerts
|

Using a Mobile Application in the Treatment of Dysregulated Anger Among Veterans

Abstract: Findings suggest that AMT + RELAX was beneficial in reducing anger symptoms and promoting efficient use of the between-session practice; however, AMT + RELAX did not outperform AMT. This study is an important contribution as it is one of the first randomized controlled trials to study the efficacy of a technology-enhanced, evidence-based psychotherapy for anger management. Findings are limited because of small sample size and modifications to the technology during the trial. However, the results highlight the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…Other study designs have shown varying degrees of improvement in PTSD symptoms associated with apps that target PTSD, 2527 and even with apps that primarily target anger and pain management. 2830 But the promising feasibility and acceptability of the app-based interventions is more consistent with previous studies. PTSD Coach in particular has been downloaded several thousand times and has received predominantly positive reviews and user satisfaction ratings, with many describing the app as helpful for improving symptoms and knowledge of PTSD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other study designs have shown varying degrees of improvement in PTSD symptoms associated with apps that target PTSD, 2527 and even with apps that primarily target anger and pain management. 2830 But the promising feasibility and acceptability of the app-based interventions is more consistent with previous studies. PTSD Coach in particular has been downloaded several thousand times and has received predominantly positive reviews and user satisfaction ratings, with many describing the app as helpful for improving symptoms and knowledge of PTSD.…”
Section: Discussionsupporting
confidence: 87%
“…PTSD Coach in particular has been downloaded several thousand times and has received predominantly positive reviews and user satisfaction ratings, with many describing the app as helpful for improving symptoms and knowledge of PTSD. 2631 These findings are also consistent with the known interest in mobile health interventions among veterans in PTSD treatment. 11…”
Section: Discussionsupporting
confidence: 82%
“…Simple bespoke UX-focused feedback offers a pragmatic and potentially efficient way to summarize perceptions concerning the UX of an existing app design. Mackintosh et al (27) examined the UX of a mobile app for the treatment of emotional dysregulation among veterans. The app had functions for practicing emotional regulation skills, monitoring symptoms as well as recording physiological data, and was used in-between face-to-face anger management therapy sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Customizable push-notification medication reminders 36 Flashing lights and beeping of electronic pill bottle 36 Discreteness of electronic pill bottle 36 Blood pressure logging 34 Weight logging 34 Education modules 34 Health-related messages to coach 34 Hypertension (n = 1) Weigh-ins 37 None reported Meal logging 37 Educational articles 37 Targeted text messages 37 Mental health (n = 10) Personalization of app content [38][39][40] Videogame-inspired cognitive intervention 13 Push notifications at 12:30 pm any day, or at 7:30 pm on weekends (vs. other times of the day) 46 Tailored health message notifications (vs. standard push notifications) are associated with a small increase in likelihood to engage with an app within 24 h 46 Graphical representation of mood states over time 38 ''Some participants appreciated the badges and reinforcements they received when they completed their check-in surveys, whereas others felt patronized by the motivational language'' 40 Prompts to use app 38 Internet-based problem-solving therapy 13 Daily health tips 13,45 Daily surveys 40,45 Alerts in response to daily surveys 40 Direct visualization of their own data 40 Using a hub recommender app 41 Expectation to swap apps in and out of use rotation 42 Low-intensity coaching 42 Skills training through brief app sessions 42 Appointment reminders 43 Tracking functions 43 Anger frequency/intensity/cues logging 44 Behavioral strategies suggestions 44 Individually tailored anger management plan prompts 44…”
Section: Discussionmentioning
confidence: 99%